Le carcinome épidermoïde : à propos de deux cas - Chirine CHAMMAS; Nadia SKANDRI; Dolly ROUKOZ (International Arab Journal of Dentistry (IAJD), 2014)
Squamous cell carcinoma accounts for over 90% of malignant tumors of the oral cavity. This type of cancer can be present in different clinical aspects and in various locations. Only early diagnosis can improve prognosis. The responsibility of the dentist is crucial when it comes to detecting and / or diagnosing such lesions promptly, the patient may benefit from a quick and appropriate treatment, and especially a better prognosis.We present two cases of squamous cell carcinoma diagnosed at early stages. The first, at the lateral edge of the ventral surface of the tongue, the second at the buccal mucosa evolving on reticular and erosive lichen planus.